Paddy Kelly, Game Keeper of the Trumpet Mountain.... - [D.N?] (Harding, 1795)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Paddy Kelly; Dundalk (Ireland); Ireland -- Social conditions -- 18th century